Triboelectric nanogenerator–based wireless sensing for food precise positioning. (November 2022) - Yang, Y.; Mu, B.; Wang, M.; Nikitina, M.A.; Zafari, U.; Xiao, X.
Abstract: The methods used to achieve food position detection in food conveyor systems rely on additional, independent external individually powered systems such as infrared radiation. The friction characteristics in conveyor systems are not well utilized. The aim of this article is to propose a low-cost triboelectric nanogenerator (TENG) position sensor for conveyor systems. Combining the unique frictional properties of the conveyor system, we propose a position detection triboelectric nanogenerator (PD-TENG) based on a wireless sensing scheme that makes full use of the frictional properties of the conveyor belt itself, where in-process position detection can be easily attached to the transport system. The PD-TENG, operating in freestanding triboelectric-layer mode, generates an alternating electrical voltage signal upon contact with the food packaging, the peak value of which is captured using an AD conversion module and judged by the MCU to achieve an accurate determination of the position of the food. The design of the PD-TENG is streamlined and offers a functional alternative to traditional infrared sensor devices and a significant reduction in cost. The output signal of the PD-TENG has been measured for different packages of food and the results show that the PD-TENG is adequate for conventional food logistics conveyor systems.